The grammar of French quantification - Baunaz, Lena (Springer Netherlands, 2011)
This book is the first extensive study on French Quantification in the field of Syntax. It provides a typology of four main quantified noun phrases in French (existential, universal, negative and wh-), detailing their syntactic, semantic and prosodic behaviors and showing that they can be reduced to two classes?Split-DP structures or Floating quantification. Relying on syntax and semantics, the book establishes a three-way structural typology of wh in-situ phrases and extends it to existentials. It pays special attention to the prosodic properties associated with their different readings and proposes an analysis of the distribution of subextraction and pied-piping. Similarly based on semantic and syntactic tests, the book reveals N(egative) words to be universal Quantifiers. It proposes a new structure of N-words in terms of constituent negation and includes a detailed analysis of the difference between not an N and not all the N in French.